2012
DOI: 10.1063/1.4763480
|View full text |Cite
|
Sign up to set email alerts
|

Driving mechanism of exchange bias and magnetic anisotropy in multiferroic polycrystalline BiFeO3/permalloy bilayers

Abstract: Magnetization reversal processes of Permalloy exchange coupled with thin polycrystalline antiferromagnetic multiferroic BiFeO3 films were investigated. The BiFeO3 critical thickness and the interfacial exchange energy are comparable with similar epitaxially grown systems. However, the coercive field dependence on multiferroic thickness presents an atypical behaviour. This system shows induced unidirectional, uniaxial, and biquadratic-like behaviour with misalignment of magnetic easy axis with respect to pinnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…According to the model proposed by Meiklejohn and Bean [34], the effective unidirectional magnetic energy is given by r = H EB M FM t FM , where H EB is exchange bias field ($105Oe at 4 K), M FM is the magnetization (at 4 K) in emu/cm 3 (for 4 mm  4 mm sample) of ferromagnetic layer of thickness (t FM ) of 45 nm. This leads to a value of r = 8.4 erg/cm 2 in our system, which is much greater than the values of 0.057 erg/ cm 2 and 0.024 erg/cm 2 reported for Py interfaced with AFM layers such as FeMn [35] and BiFeO 3 [36], respectively. This is too large to explain with interfacial uncompensated spins.…”
Section: Introductionmentioning
confidence: 56%
“…According to the model proposed by Meiklejohn and Bean [34], the effective unidirectional magnetic energy is given by r = H EB M FM t FM , where H EB is exchange bias field ($105Oe at 4 K), M FM is the magnetization (at 4 K) in emu/cm 3 (for 4 mm  4 mm sample) of ferromagnetic layer of thickness (t FM ) of 45 nm. This leads to a value of r = 8.4 erg/cm 2 in our system, which is much greater than the values of 0.057 erg/ cm 2 and 0.024 erg/cm 2 reported for Py interfaced with AFM layers such as FeMn [35] and BiFeO 3 [36], respectively. This is too large to explain with interfacial uncompensated spins.…”
Section: Introductionmentioning
confidence: 56%
“…Therefore, it is of interest to study the exchange bias properties not only in epitaxial systems but also in polycrystalline ones . Following this, we have recently demonstrated that an exchange coupling may be induced in polycrystalline BiFeO 3 /Ni 80 Fe 20 (Py/BFO) bilayers [7,8] . At 300 K, the interfacial exchange coupling energy in the polycrystalline BFO/Py bilayers is similar to those reported in previously studied epitaxial BFO/F bilayers [9][10][11] .…”
mentioning
confidence: 77%
“…[1][2][3] The exchange bias effect is the most studied phenomenon induced by exchange coupling, and the bias field has been found to be inversely proportional to the FM layer thickness (d FM ), which indicates the interfacial character of the exchange coupling. [4][5][6][7][8][9][10][11] Due to the lack of information on the AFM layer and FM/AFM interface, the detailed mechanism of exchange coupling is still under debate. 2,3 Exchange coupling can also induce a uniaxial anisotropy in the FM layer, 2,3 associated with an enhancement of the coercivity field (H C ).…”
Section: Introductionmentioning
confidence: 99%